Longitudinal effects of evidence-based physical education in Maltese children. Issue Volume 4:Issue1(2021) (1st January 2021) - Fenech, Amanda; Chockalingam, N.; Formosa, C.; Gatt, A.
ABSTRACT: Background: Malta is an obesogenic country with low levels of daily moderate-to-vigorous physical activity (MVPA) reported amongst Maltese children. Schools play a significant cost-effective role in delivering and encouraging physical activity and thus contributing to population health. So far, there were no specific school-based physical activity interventions in Malta. This creates a public health action gap. The study will assess the feasibility of Maltese children engaging in MVPA in more than 50% of Physical Education lesson time through an evidence-based PE curriculum. Its longitudinal effects on school children's anthropometric factors, cardiorespiratory fitness and biomechanical variables are evaluated.Methods: One-hundred twenty 9-to-10-year-old children, attending state primary schools, participated in a time-series study design over one scholastic year. The intervention group (n = 76) had Sports, Play and Active Recreation for Kids (SPARK) PE curriculum. The control group (n = 44) was taught the national PE curriculum. The functional outcome measures included vertical jump height and posturography. Lesson MVPA levels were measured with the System for Observing Fitness Instruction Time (SOFIT). Other measurements included: BMI z-scores, waist circumference and resting heart rate (RHR).Results: Achievement of >50% of PE lesson time in MVPA intensity is feasible through an evidence-based PE curriculum (60.43% from a baseline of 36.43% in intervention group vs 39.06% from a baseline of 39.89% in control). The intervention group reported improvements in BMI z-scores (p = 0.007; CI = 0.02, 0.15), RHR (p = 0.009; CI = 1.10, 7.46), balance parameters and jump height (p = 0.020; CI = −2.42, −0.23).Conclusions: MVPA levels were successfully increased through the evidence-based physical education curriculum with resultant positive health effects. Force platform analysis allows objective fitness monitoring in schoolchildren. This study recommends the integration of evidence-based PE curricula as a public health initiative against childhood obesity.